PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN TIPE TWO STAY TWO STRAY (TSTS) PADA MATERI PERSEGI PANJANG DAN PERSEGI DI KELAS VII SMP IT AL-HIJRAH DELI SERDANG TAHUN PELAJARAN 2 - Reziono Pratama; Sajaratud Dur (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
This research aims to know different learning outcomes student's thatlearned using cooperative model type Group Investigation (GI) and typeTwo Stay - Two Stray (TSTS) in rectangular and square subject at VIIClass SMP IT Al-Hijrah Deli Serdang T.A. 2015/2016. This isquantitative research type quasi experiment research. The populationare all students at VII class of SMP IT Al-Hijrah Deli Serdang T.A.2015/2016 that totaled 42 students. The sample in this research are 21students of VII-A class and 21 students of VII-B class. The method ofdata analysis is used Analysis Varian (ANAVA). The result is: 1) thelearning outcomes student's that learned using cooperative learningtype TSTS is better than learning outcomes student's that learned usingcooperative learning type GI in rectangular and square subject. 2) thelearning outcomes student's with high ability that learned usingcooperative learning type TSTS is better than learning outcomesstudent's that learned using cooperative learning type GI in rectangularand square subject. 3) the learning outcomes student's with low abilitythat learned using cooperative learning type TSTS is better thanlearning outcomes student's that learned using cooperative learningtype GI in rectangular and square subject. 4) There is no significantinteraction between learning strategy and student's ability to learningoutcomes student's in rectangular and square subject. The conclusion ofthis research is explain that high ability student's and low abilitystudent's more suitable if learned using cooperative learning modelwith type Two Stay Two Stray (TST) in rectangular and square subjectat VII class SMP IT Al - Hijrah Deli Serdang.